Report of the internally commissioned external review of the CGIAR genebank operations - CGIAR Systemwide Genetic Resources Programme (1996)
In 1995 the SGRP commissioned an External Review of the CGIAR Centre Genebank Operations. This review was conducted by a panel and involved 20 experts from national and regional genetic resources programmes, including the United Nations Food and Agriculture Organization (FAO). The purpose of this review was to assess the technical, scienetific and financial constraints facing the Centre genebanks and to identify opportunities for improving their operations and the services they provide. This synthesis report contains overall recommendations and the collective response of the Inter-Centre Working Group on Genetic Resources to these recommendations.